Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/dev.20613
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of differential early rearing in rhesus macaques: Behavioral reactivity in adulthood

Abstract: Adverse early experiences are associated with a range of deleterious health outcomes in humans, including higher risk for affective disorders. Studies using a long-standing model of nonhuman primate model of early adversity have demonstrated that nursery-reared monkeys exhibit alterations in multiple aspects of biobehavioral development; however, few studies have evaluated the persistence of socioaffective behavioral changes through adulthood. We evaluated the effects of early rearing experience on adult anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 106 publications
1
44
0
1
Order By: Relevance
“…Nursery-rearing in nonhuman primates has been shown to result in behavioral and neurochemical changes later in life consistent with affective disorders, and these animals have been reported to consume greater quantities of ethanol relative to MR animals (Harlow et al, 1959; Harlow et al, 1965; Harlow & Suomi, 1974; Seay & Harlow, 1965; Suomi, 1997; Shannon et al, 1998; Sanchez et al, 2001; Machado & Bachevalier, 2003; Cirulli et al, 2009; Higley et al, 1991). Consistent with this, a parallel study using the mother-reared (MR) and nursery-reared (NR) ethanol-naïve monkeys that were also used in the current study reported altered socioaffective behavior in NR monkeys compared to MR monkeys (Corcoran et al, 2011). This model thus provides a unique resource to understand neurobiological changes similar to those that may occur in human children exposed to early-life stress and how these changes may contribute to the development of addictive behaviors later in life.…”
Section: Introductionsupporting
confidence: 75%
“…Nursery-rearing in nonhuman primates has been shown to result in behavioral and neurochemical changes later in life consistent with affective disorders, and these animals have been reported to consume greater quantities of ethanol relative to MR animals (Harlow et al, 1959; Harlow et al, 1965; Harlow & Suomi, 1974; Seay & Harlow, 1965; Suomi, 1997; Shannon et al, 1998; Sanchez et al, 2001; Machado & Bachevalier, 2003; Cirulli et al, 2009; Higley et al, 1991). Consistent with this, a parallel study using the mother-reared (MR) and nursery-reared (NR) ethanol-naïve monkeys that were also used in the current study reported altered socioaffective behavior in NR monkeys compared to MR monkeys (Corcoran et al, 2011). This model thus provides a unique resource to understand neurobiological changes similar to those that may occur in human children exposed to early-life stress and how these changes may contribute to the development of addictive behaviors later in life.…”
Section: Introductionsupporting
confidence: 75%
“…Finally, the present study focused on infants who were raised by human caretakers. This unique rearing may have impacted infants’ early OT systems (Corcoran et al 2012; Winslow et al 2003); studies in mother-reared infants are necessary to determine the generalizability of our results. Nonetheless, the present results extend previous findings of positive social effects of OT in infant monkeys (Simpson et al 2014), suggesting OT effects also appear in more cognitive tasks.…”
Section: Discussionmentioning
confidence: 95%
“…Macaques reared in sub-optimal mother-only conditions show higher fear and anxiety responses to a stress-inducing challenge than those from rearing conditions in which multiple adults and peers are present [1]. These affective responses, also characterized by pronounced behavioral inhibition, in SOR-exposed macaques persist well into adulthood [4]. Some behavioral effects of ELSA may not be long lasting, as macaques that experienced STS as infants displayed normative behavioral reactivity when placed in short-term social isolation as adults [5].…”
Section: Developmental Outcomesmentioning
confidence: 99%